A new type of solid-state luminescent 2-phenylbenzo[g]furo[2, 3-b]quinoxaline derivative: synthesis, photophysical characterization and transporting properties. Issue 31 (25th July 2019) - Wang, Gang; Li, Jie; Li, Yixiang; Wang, Dongdong; Zhang, Jingjing; Wu, Yong; Zhen, Yong-gang; Tang, Qingxin; Ma, Hong; Hu, Wenping; Wu, Zhaoxin; Jen, Alex K.-Y.
Abstract : We developed a new synthesis method of furo [2, 3- b ] quinoxaline core and report a new type of 2-phenylbenzo[ g ]furo [2, 3- b ] quinoxaline organic semiconductors, which shows 22.1% PLQY in solid powders and hole mobility of 2.58 × 10 −2 cm 2 V −1 s −1 . Abstract : Organic semiconductors combining high mobility and efficient solid fluorescence are in high demand for developing organic light-emitting transistors and electrically driven organic lasers. But, achieving such dual functional molecules is extremely challenging. In this manuscript, we report 2-phenylbenzo[ g ]furo[2, 3- b ]quinoxaline derivatives (3a–3c ) and develop a new synthesis method for the furo[2, 3- b ]quinoxaline core. It was found that3a exhibited favorable aggregation induced emissive enhancement behavior and reasonable hole mobility. The absolute photoluminescence quantum yield of3a is determined to be 22.1% in solid powders and can reach a maximum of 19.7% in 50% water in THF, twice that in CH2 Cl2 solution (9.2%) and dispersed in PS film (9.3%). The single crystal and thin film organic field-effect transistor of3a show a hole mobility of 2.58 × 10 −2 cm 2 V −1 s −1 and 5.7 × 10 −3 cm 2 V −1 s −1, respectively. Our results demonstrated that the 2-phenyl-benzo[ g ]furo[2, 3- b ]quinoxaline skeleton is a promising candidate for building multifunctional organic optoelectronics.